2016
DOI: 10.1371/journal.pone.0155582
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Oil Phase and Topical Formulation on the Wound Healing Ability of a Birch Bark Dry Extract

Abstract: Triterpenes from the outer bark of birch are known for various pharmacological effects including enhanced wound healing (WH). A birch bark dry extract (TE) obtained by accelerated solvent extraction showed the ability to form oleogels when it is suspended in oils. Consistency of the oleogels and the dissolved amount of triterpenes varies largely with the used oil. Here we wanted to know to what extent different oils and formulations (oleogel versus o/w emulsion) influence WH. Looking at the plain oils, medium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
(36 reference statements)
2
26
0
Order By: Relevance
“…Also under hyperglycaemic conditions TE did not improve scratch WH in-vitro . However, there was a stimulating effect on reepithelialization in ex-vivo WH models under hyperglycaemic conditions, similar to what was shown in ex-vivo models and in-vivo under euglycaemic conditions[22, 24]…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Also under hyperglycaemic conditions TE did not improve scratch WH in-vitro . However, there was a stimulating effect on reepithelialization in ex-vivo WH models under hyperglycaemic conditions, similar to what was shown in ex-vivo models and in-vivo under euglycaemic conditions[22, 24]…”
Section: Introductionsupporting
confidence: 65%
“…The non-existing or even negative effect of TE and betulin on in-vitro WH under euglycaemic conditions was surprising because the extract positively influences WH i n-vivo and ex-vivo [2224]. Therefore, we concluded that this beneficial effect is dependent on the interplay with other cells.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…MCT shows good wound-healing properties even without TE. Oleogels with sunflower oil improve wound healing significantly [25]. Paraffin was used as non-polar reference.…”
Section: Introductionmentioning
confidence: 99%